Microstructure and elevated-temperature tensile properties of differential pressure sand cast Mg-4Y-3Nd-0.5Zr alloy - Liu, Hong-hui; Ning, Zhi-liang; Sun, Hai-chao; Cao, Fu-yang; Wang, Hao; Zhao, Xin-yi; Sun, Jian-fei (China foundry, 2016)
The microstructures of an Mg-4Y-3Nd-0.5Zr alloy by differential pressure casting were investigated using scanning electron microscopy （SEM） and transmission electron microscopy （TEM）, and its tensile deformation behavior was measured using a Gleeble1500D themo-simulation machine in the temperature range of 200 to 400 ℃ at initial strain rates of 5×10^-4 to 10^-1 s^-1. Results show that the as-cast microstructure consists of primary α-Mg phase and bone-shaped Mg5RE eutectic phase distributed along the grain boundary. The eutectic phase is dissolved into the matrix after solution treatment and subsequently precipitates during peak aging. Tensile deformation tests show that the strain rate has little effect on stress under 300 ℃. Tensile stress decreases with an increase in temperature and the higher strain rate leads to an increase in stress above 300 ℃. The fracture mechanism exhibits a mixed quasi-cleavage fracture at 200 ℃, while the fracture above 300 ℃ is a ductile fracture. The dimples are melted at 400 ℃ with the lowest strain rate of 10^-4 s^-1.